2013
DOI: 10.1249/mss.0b013e3182843961
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Lifestyle Modification Reduces Lp-PLA2 in Dyslipidemic HIV/HAART Patients

Abstract: Patients with dyslipidemia associated with HIV-1 infection and highly active antiretroviral therapy (HAART) have elevated levels of Lp-PLA2 and CCL5/RANTES, which may increase risk of cardiovascular disease. Purpose This study aimed to determine whether an intensive diet and exercise (D/E) program, independently or combined with fenofibrate or niacin, could reduce Lp-PLA2 or RANTES. Methods Hypertriglyceridemic HIV patients on stable HAART (n=107) were randomized to one of five interventions: 1) Usual Care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
4
19
0
Order By: Relevance
“…After controlling for confounders, increased hsCRP levels and T2DM with hypertriglyceridemia were independently related to high serum RANTES levels. Our findings agree with studies indicating that circulating RANTES was significantly higher in patients with hypertriglyceridemia [ 23 ] or with T2DM [ 24 ] compared with controls, and was positively related to FBG [ 25 ]. Furthermore, our finding that serum RANTES was positively associated with Hcy support our previous result that the circulating RANTES levels were elevated in hyperhomocysteinemia patients compared with controls [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…After controlling for confounders, increased hsCRP levels and T2DM with hypertriglyceridemia were independently related to high serum RANTES levels. Our findings agree with studies indicating that circulating RANTES was significantly higher in patients with hypertriglyceridemia [ 23 ] or with T2DM [ 24 ] compared with controls, and was positively related to FBG [ 25 ]. Furthermore, our finding that serum RANTES was positively associated with Hcy support our previous result that the circulating RANTES levels were elevated in hyperhomocysteinemia patients compared with controls [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is similar to our previous results that RANTES levels were significantly higher in type 2 diabetes patients with hypertriglyceridemia compared with controls [8], and aligns with some other studies indicating that circulating RANTES levels were significantly higher in patients with dyslipidemia [21], hyperglycemia [22, 23], or metabolic syndrome [24] compared with controls. Our present study also documented that PFP RANTES levels were positively correlated with the levels of TC, TG, FBG, 2hPG, and HbA1c, but negatively related to the levels of HDL-C, which supported that RANTES might be associated with disorders of metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with the results obtained in vitro, several in vivo studies have demonstrated increased PLA 2 activation, as well as higher levels of AA and its metabolites, in HIV-1-infected individuals. In particular, these patients, compared with healthy controls, presented with higher plasma sPLA 2 and Lp-PLA 2 levels or increased enzymatic activity, associated with an enhanced risk of cardiovascular disease [199][200][201][202][203][204]. The effect of different antiretroviral regimens on plasma Lp-PLA 2 levels was investigated by several groups [205][206][207][208][209][210][211].…”
Section: Plcs In Hiv-1 Infectionmentioning
confidence: 99%